Carotid artery access for transcatheter aortic valve replacement. Issue 4 (28th March 2013) - Guyton, Robert A.; Block, Peter C.; Thourani, Vinod H.; Lerakis, Stamatios; Babaliaros, Vasilis
<x xml:space="preserve">Abstract</x> We report three patients who had successful transcatheter aortic valve replacement (TAVR) via carotid artery access. None were candidates for thoracotomy (including minimal access incisions) and had no other vascular access sites that would accommodate the transcatheter valve sheath. Antegrade carotid perfusion and retrograde insertion of the delivery sheath maintained cerebral blood flow without sequelae. Carotid access for TAVR is an option for unusual patients without other access. © 2012 Wiley Periodicals, Inc.